Equivalence, Variation, and Lacunarity of Diagnostic Nominations in the Russian and Uzbek Versions OF ICD-11: Linguocognitive and Pragmatic Mapping - Alisher Anvarjon o‘g‘li To‘rayev (CV. Media Digital Publikasi Indonesia, 2026)
ICD-11 is a multilingual digital classification in which a stable conceptual identifier is accompanied by language-specific diagnostic labels. This article argues that Russian-Uzbek ICD-11 comparison should be evaluated through three interrelated levels: conceptual preservation, nominative realization, and pragmatic suitability. A stratified exploratory sample of 148 Russian-Uzbek diagnostic pairs from the 2025-01 release was analysed through comparative, structural-semantic, componential, frame-based and register-oriented pragmatic procedures. Formally international correspondences constituted 55.4% of the sample; structural calques and mixed forms, 29.7%; conventional national forms, 8.1%; descriptive-explicative forms, 5.4%; and abbreviation transformations, 1.4%. Nine cases of variation and nine nominative lacunae were identified. Conceptual lacunae were not recorded within the sample because all compared pairs were aligned through the same ICD-11 entity. The proposed map links the ICD-11 identifier, preferred terms, variants, frame slots, register and patient-oriented explanation. It is presented as an analytical procedure rather than as a statistically universal typology.